(untitled) - Powell, Ronald R. (Westport, Conn., 2004)
This revision of Basic Research Methods for Librarians provides substantially expanded content and adds Lynn Sillipigni Connaway as co-author with Ronald R. Powell, who was sole author of the first three editions....[B]asic Research Methods for Librarians....[i]s the textbook for research methods courses in schools of library and information studies. It may also be useful to very motivated self-teachers. Anyone with an abiding interest in library and information science research should have this book (Editoral review)
Keywords: Library science,Thư viện học; Research,Methodology,Nghiên cứu,Phương pháp luận